Carbon Emissions and Climate Change Disclosure in Low-Carbon Companies in Indonesia - Krisnina Maharani Putri Baiq; Ely Windarti Hastuti; Animah; Ulaya Fitriani Baiq (Agregat: Jurnal Ekonomi dan Bisnis, 2026)
This study aims to understand how Low Carbon Leader companies integrate sustainability aspects, specifically carbon emission disclosure, climate change disclosure, environmental performance, and their impact on company value. The population used in this study consists of all companies listed in the Low-Carbon Leader Index on the Indonesia Stock Exchange, selected using a purposive sampling approach, comprising 24 companies with a 3-year mandate period (2022-2024). This study uses a quantitative approach, with panel data regression analysis processed using E-views software version 12. The results of this study indicate that carbon emission and climate change disclosures have a negative effect on company value, and only environmental performance has a positive effect on the company value of low-carbon leader companies. This finding supports the legitimacy theory in explaining the relationship between environmental performance and capital market reactions. Investors respond more to substantive legitimacy reflected in real and measurable environmental performance, such as through the PROPER rating, compared to symbolic environmental disclosures. Practically, this study's findings have implications for how investors and companies consider and evaluate the size and indicators of environmental issues as important considerations for future corporate sustainability initiatives